Export, FDI and firm productivity - Dirk Engel; Vivien Procher (Applied Economics, 2012)
Many empirical papers tested the theoretical predictions of Helpman, Melitz and Yeaple (HMY, 2004) which sorts firms at different internationalization states according to their productivity levels. While these papers ignore the fact, that the theoretical predictions of HMY only apply to firms that become engaged in market-driven Foreign Direct Investment (FDI), we apply a more precise methodology using a French firm sample with more than 1100.167em000 observations. Our results show that firms with a broader investment strategy, reflecting a great importance of market-driven motives, show higher productivity levels than firms with less encompassing foreign investment strategies. We conclude that the methodology is well-suited to sort firms according to the importance of market-driven FDI.
Keywords: F10; F23; D21; D24; 330; foreign direct investment; multinational enterprises; productivity